Justice, Expediency, and Legal Certainty In Constitutional Court Decision Number 90/PUU-XXI/2023 - Wira Atma Hajri; Ellydar Chaidir; Suparto; Suparto (International Conference On Law And Social Sciences, 2024)
Ideally, every decision made by judges, including Constitutional Judges, should pay attention to the impact that will be caused considering that the decision is final. The Constitutional Court Decision Number 90/PUU- XXI/2023 concerning the Examination of Law Number 7 of 2017 concerning General Elections regarding the age threshold for president and vice president candidates have give some experience for the election in Indonesia. In previous decisions with the same object, namely Decision Number 29/PUU-XXI/2023, Decision umber 51/PUU-XXI/2023, and Decision Number 55/PUU-XXI/2023, the Constitutional Court is of the view that the age threshold for president and vice president candidates is a matter of open legal policy that became the authority from House of Representatives and the President. However, in Decision Number 90/PUU-XXI/2023, the Constitutional Court changed the decision with the general election process was underway by allowing under the age of 40 (fourty) with a record of having or currently occupying positions elected through general elections including regional head elections. In the end, the polemic situation have get a attention by public for the justice, expediency, and legal certainty of the Constitutional Court Decision Number 90/PUU- XXI/2023 considering that this decision will be directly applied in the 2024 general election. This is different if the Constitutional Court declares Constitutional Court Decision Number 90/PUU-XXI/2023 to apply to the 2029 general election.